2002
DOI: 10.1046/j.1460-9592.2002.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of postdural puncture headache with epidural blood patch in children

Abstract: EBP gave some relief of symptoms in all children. No complications related to EBP were noticed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
4
32
0
1
Order By: Relevance
“…19,20 Like adults, pediatric patients (girls > boys) may develop postdural puncture headache after diagnostic spinal punctures, spinal anesthesia, or inadvertent dural puncture after attempted epidural needle placement. An initial epidural blood patch using 0.2 to 0.3 mL·kg -1 of autologous blood completely abolished postural headache in more than 90%, 19,20 while a second epidural blood patch was effective in the remainder. In contrast to these observations, our patient did not sustain a needle punctureinduced dural injury, but rather suffered a larger (0.5 cm) durotomy as a complication of microdiscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Like adults, pediatric patients (girls > boys) may develop postdural puncture headache after diagnostic spinal punctures, spinal anesthesia, or inadvertent dural puncture after attempted epidural needle placement. An initial epidural blood patch using 0.2 to 0.3 mL·kg -1 of autologous blood completely abolished postural headache in more than 90%, 19,20 while a second epidural blood patch was effective in the remainder. In contrast to these observations, our patient did not sustain a needle punctureinduced dural injury, but rather suffered a larger (0.5 cm) durotomy as a complication of microdiscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is often empirical and can be attributed to several variables other than CSF leakage [3,11]. An autologous "blood patch" (EBP) is standard secondtier therapy for persistent PDPH [3,4,[12][13][14]. The "patch," an outpatient procedure, consists of an epidural being performed; blood is then drawn under sterile conditions from the patient's arm vein and injected into the epidural space via the epidural needle to "seal" any CSF leakage from the suspected perforation site.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of patients with persistent headache after an epidural blood patch was decreased when compared to patients receiving conservative treatment ( p = 0.03). An additional three retrospective chart review studies reported that the use of an epidural blood patch was effective in relieving post-lumbar puncture headaches in a high percentage of patients (Kokki, Sjovall, & Kokki, 2012; Ylonen & Kokki, 2002 A ; Ylonen & Kokki; 2002 B ). Four case studies also supported this trend (Cassady, Lederhaas, Turk, & Shanks, 2000; Kara et al, 2012; Liley et al, 2003; Roy, Vischoof, & Lavoie, 1995).…”
Section: Evidence Reviewmentioning
confidence: 99%